Optimal urea level in corn-based finishing diets containing alfalfa as the roughage source - C.T. Milton; Robert T. Brandt Jr. (Kansas Agricultural Experiment Station Research Reports, 1995)
One hundred medium-growth potential, crossbred yearling steers (766 lb) were used to identify the optimal level of urea in finishing diets, based on growth and carcass traits. The corn-base d diets had no urea o r contained .35, .70, 1.05, or 1.40% urea (dry matter basis) and no other supplemental protein. Alfalfa hay (10% of DM) was the roughage source and contained 16% crude protein. Feed efficiency and gain were improved by .35% urea, with little improvement from higher additions. Regression analysis indicated that the optimal level of urea for gain and feed efficiency was .5% of dietary dry matter. Hot carcass weight and dressing percentage responded quadratically, being highest for steers receiving .7 and 1.05% urea. Fat thickness and yield grade responded cubically to the addition of urea; these traits were also highest for steers receiving .7 and 1.05% urea. Loineye area decreased linearly with increased urea in the diet. Marbling scores and KPH fat were unaffected by urea addition. The increased growth, carcass weight, and finish, with no improvements in loineye area, indicate that urea enhance d diet digestibility but did not increase metabolizable protein supply. Optimal urea levels (.5%) were less than those previously indicate d for diets containing prairie hay as the roughage source (.9%), suggesting that alfalfa may supply a portion of the rumen degradable nitrogen requirement when utilized as a source of roughage in high grain diets.
Keywords: Cattlemen& #x27; s Day; 1995; Kansas Agricultural Experiment Station contribution; no. 95-357-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 727; Beef; Urea; Finishing steers; Performance; Metabolizable protein